Development and characterization of Pleurotus ostreatus mushroomwheat bread - Losoya-Sifuentes, C. (2022)
The Pleurotus ostreatus mushroom is a source of high nutritional value and bioactive compounds such as -glucans, with immunomodulatory, hypoglycemic and prebiotic activity. The aim of this work was to developed a bread with P. ostreatus powder (POP) to increase its nutritional value and reduce its glycemic index. Four formulations were proposed substituting 5, 10, 15 and 20% of wheat flour (w/w) for POP in the bread and their physical characteristics and nutritional were evaluated. In addition to determining the glycemic index and the in vitro digestion of starch in the proposed formulations. Results shown that with the addition of POP the specific volume of the bread decreased, and it became darker. The nutritional value of the bread was enriched, since the content on proteins, fiber and minerals increased. The results of in vitro simulated gastrointestinal digestion demonstrated that bread supplemented with POP showed more optimal starch digestibility with slower digestion rate, lower eGI and RDS contents, which could bring health benefits to humans. These findings suggest that the mushroom powder is an excellent alternative to produce bread with improved nutritional quality and decreased glycemic index.